2017
DOI: 10.1016/s2468-2667(17)30045-2
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of key demand-reduction measures of the WHO Framework Convention on Tobacco Control and change in smoking prevalence in 126 countries: an association study

Abstract: Health Canada, Canadian Institutes of Health Research, Ontario Institute for Cancer Research and Canadian Cancer Society Research Institute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
157
4
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(173 citation statements)
references
References 12 publications
(14 reference statements)
9
157
4
3
Order By: Relevance
“…Lessons can be learned from 10 years of implementing WHO FCTC and the demonstrated benefit in combating noncommunicable diseases (17,18). Cairney and Mamudu (19) report that the best approach to tobacco control in a country requires specific policy processes, namely: the department of health takes the policy lead; tobacco is 'framed' as a public health problem; public health groups are consulted at the expense of tobacco control interests; socioeconomic conditions are conducive to policy change; and the scientific evidence is 'set in stone' within governments.…”
Section: Introductionmentioning
confidence: 99%
“…Lessons can be learned from 10 years of implementing WHO FCTC and the demonstrated benefit in combating noncommunicable diseases (17,18). Cairney and Mamudu (19) report that the best approach to tobacco control in a country requires specific policy processes, namely: the department of health takes the policy lead; tobacco is 'framed' as a public health problem; public health groups are consulted at the expense of tobacco control interests; socioeconomic conditions are conducive to policy change; and the scientific evidence is 'set in stone' within governments.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research found that full implementation of tobacco taxes, smoke-free laws, advertising bans, and cessation support, through robust legislation and rigorous enforcement did result in substantial declines in prevalence 6. The more measures were fully implemented, the greater the rate of decline.…”
Section: Framework Convention On Tobacco Controlmentioning
confidence: 99%
“…In that analysis of 126 countries, those countries that implemented a greater number of these key demand-reduction policies of the FCTC (Articles 6, 8,11,13,14) at the highest level experienced a significantly greater reduction in smoking rates: equal to 7.09% relative decrease in smoking rates for each additional policy implemented over the first decade of the treaty (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). (8) In the case of Korea, only one policy was fully implemented (cessation: Article 14). If the other 4 policies had been fully implemented, the expected reduction in smoking rates would be 4×7.09% relative reduction=28.4%.…”
mentioning
confidence: 99%